B. BRAUN PRESIDENT VISITS AMDI HOSPICE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
BERTAM, 14 July 2015 The President of B. Braun Medical Industries Sdn. Bhd. for Asia Pacific Region, Anna Maria Braun visited the Universiti Sains Malaysia (USM) Advanced Medical and Dental Institute (AMDI) to take a firsthand look at the cancer patient care services otherwise known as Hospice Care, here today.